Semantyczno-pragmatyczne znaczenie natury - Jacek L. Łapiński (Studia Ecologiae et Bioethicae)
Semantic meaning of the term „nature” comes from the Latin word „nasci” - „to get born”, and Greek words „physis” and „arche”, the substance of the latter two terms is fully explained in the Latin dictionary of A. Forcellini (Klotius Latinitatis Lexicon, 4, Prati 1868, p. 231-232) and the Greek-English dictionary of H. G. Liddell and R. Scott (Greek-English Lexicon, The Clarendon Press, Oxford 1940, 1958, p. 1964-1965.).